IgG4 related disease masquerading as a sinonasal mass: a case report and review of literature - Krishnan, Meenu; Rangachari, Vijay; Katti, Sanjeev; Channabasappa, Yathish G.; H. Rakshit, Susmita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
IgG4-related disease (IgG4-RD) is a relatively new autoimmune fibroinflammatory disease. Most seen to affect the pancreas and biliary tract, IgG4-RD of the nose and paranasal sinuses is very rare. Known to have tumour-like clinical presentations, they can present with varying levels of dysfunction of the organs they affect. In the paranasal sinuses, it can present with nasal block, discharge, bleeds, and sometimes, with symptoms that arise as a consequence of bony erosions and subsequent extension of the disease. We present a case of a 52-year-old lady, who presented with a painful swelling over the malar region with discoloration of the overlying skin. Radiological evaluation helps to check for bony erosions and soft tissue infiltration. Histopathology with immunohistochemistry helps to confirm the diagnosis of IgG4-RD. Most patients benefit from a long course of oral steroids and regular follow-ups, that help to prevent recurrence and ensure a good quality of life for the patient.